Student mastery of scientific inquiry skills: a preliminary study - Omar, S. S. (Serials Publications, 2017)
This paper intended to investigate student's mastery of Scientific Inquiry Skills (SIS) among form-four science stream students. The test conducted in this study was administrated by the researchers, involving a total of 30 respondents that was selected with purposive sampling method from a school in Pahang. The instrument used in this study was The Test of Scientific Inquiry Skills (TSIS), a paper and pencil multiple-choice test to measure the acquisition of the integrated science process skills in terms of, identifying variables, formulating hypotheses, interpreting data, defining operationally and designing investigation. The measurement of TSIS was based on the two thirds benchmark by previous researcher (Mohd Al-Junaidi and Ong, 2013; Mohd Najib and Abdul Raof, 2011; Sharifah Nor Ashikin and Rohaida, 2005). The findings of the study revealed that, the students' acquisition for each of the specific SIS was 65.63% for identifying variables, 62.38% for formulating hypothesis, 88.89% for interpreting data, 73.33% and 61.43% for operationally defining and designing investigation, respectively.